Profile of patients attended in the Exam and Screening Sector of the Dentistry Faculty of Universidade de Passo Fundo, Rio Grande do Sul, Brazil - Daiane Amarante de Mattos; Adriane Lehnen; Micheline Sandini Trentin; Soluete Oliveira da Silva; João Paulo de Carli; Maria Salete Sandini Linden (Faculdade São Leopoldo Mandic, 2009)
Objectives: The aim of this study is to describe the systemic diseases and dental treatment needs that most frequently affect the population of Passo Fundo, Rio Grande do Sul, Brazil and region, in patients attended at the Examination, Urgency and Screening Service of the Dentistry Faculty of the Passo Fundo University, and demonstrate their epidemiological profile. Methods: 1002 dental records filled in during patient screening from 2003 to 2006, were randomly evaluated as regards data related to gender, age, skin color, medication use, systemic alterations, reason for consultation and dental treatment of patients. The data was statistically analyzed by descriptive statistics of frequency and the chi-square test at 5%.Results: It was observed that the majority of patients attended at the Dentistry Faculty of the Passo Fundo University were: women (62%); caucasian (86%); and were in the third decade of life (19%); used various medications, mainly anti-hypertensive, analgesics and contraceptives, and presented systemic changes, such as gastritis and hypertension. The patients' main complaints were generally not related to treatment needs; individuals sought attendance mainly for prosthetic reasons or because of pain, and were referred to various dental specialties. Conclusion: Detailed clinical pre-treatment examination was shown to be important in making it possible to identify diseases, history of drugs used by patients, and aspects that could interfere or even limit dental treatments.